Prefrontal Hemodynamics in Toddlers at Rest: A Pilot Study of Developmental Variability - Anderson, Afrouz A.; Smith, Elizabeth; Chowdhry, Fatima A.; Thurm, Audrey; Condy, Emma; Swineford, Lauren; Manwaring, Stacy S.; Amyot, Franck; Matthews, Dennis; Gandjbakhche, Amir H. (Frontiers in Neuroscience, 2017)
Functional near infrared spectroscopy (fNIRS) is a non-invasive functional neuroimaging modality. Although it is amenable to use in infants and young children, there is a lack of fNIRS research within the toddler age range. In this study, we used fNIRS to measure cerebral hemodynamics in the prefrontal cortex (PFC) in 18-36 months old toddlers (n=29) as part of a longitudinal study that enrolled typically-developing toddlers as well as those “at risk” for language and other delays based on presence of early language delays. In these toddlers, we explored two hemodynamic response indices during periods of rest during which time audiovisual children’s programming was presented. First, we investigate Lateralization Index, based on differences in oxy-hemoglobin saturation from left and right prefrontal cortex. Then, we measure oxygenation variability (OV) index, based on variability in oxygen saturation at frequencies attributed to cerebral autoregulation. Preliminary findings show that lower cognitive (including language) abilities are associated with fNIRS measures of both lower OV index and more extreme Lateralization index values. These preliminary findings show the feasibility of using fNIRS in toddlers, including those at risk for developmental delay, and lay the groundwork for future studies.